2009
DOI: 10.2353/ajpath.2009.090133
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD11b+ Macrophages in Intraperitoneal Lipopolysaccharide-Induced Aberrant Lymphangiogenesis and Lymphatic Function in the Diaphragm

Abstract: Lymphatic vessels in the diaphragm are essential for draining peritoneal fluid, but little is known about their pathological changes during inflammation. Here we characterized diaphragmatic lymphatic vessels in a peritonitis model generated by daily i.p. administration of lipopolysaccharide (LPS) in mice. Intraperitoneal LPS increased lymphatic density, branching, sprouts, connections, and network formation in the diaphragm in time-and dose-dependent manners. These changes were reversible on discontinuation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 34 publications
5
125
0
1
Order By: Relevance
“…3A). TNF-␣ is induced by LPS, which also significantly affects lymphatic function (5,26). To assess whether the relative levels of miR-9 are increased in vivo in the lymphatic tissues under systemic inflammatory conditions as induced by LPS, we determined the expression of miR-9 in mesenteric lymphatic vessels isolated from normal rats and rats treated intraperitoneally with LPS for 24 h. Figure 3B shows that LPS causes a significant induction in the relative levels of IL-1␤, IL-6, MCP-1, c-fos, and MIP-2 in mesenteric lymphatic vessels, suggesting widespread inflammatory signaling in the mesentery of LPS-injected rats.…”
Section: Mir-9 Is Induced In Lecs In Vitro and In Inflamed Lymphaticmentioning
confidence: 99%
“…3A). TNF-␣ is induced by LPS, which also significantly affects lymphatic function (5,26). To assess whether the relative levels of miR-9 are increased in vivo in the lymphatic tissues under systemic inflammatory conditions as induced by LPS, we determined the expression of miR-9 in mesenteric lymphatic vessels isolated from normal rats and rats treated intraperitoneally with LPS for 24 h. Figure 3B shows that LPS causes a significant induction in the relative levels of IL-1␤, IL-6, MCP-1, c-fos, and MIP-2 in mesenteric lymphatic vessels, suggesting widespread inflammatory signaling in the mesentery of LPS-injected rats.…”
Section: Mir-9 Is Induced In Lecs In Vitro and In Inflamed Lymphaticmentioning
confidence: 99%
“…Both the increase of interstitial pressure and flow, as well as the change in cytokines and inflammatory mediators, stand to influence this drainage, yet the latter is only beginning to be explored [38,39]. Transmural flow itself can activate the lymphatic endothelium, increasing fluid and solute permeability and uptake as well as upregulating adhesion molecules required for immune cell transmigration [40].…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…However, their lineage tracing studies definitely excluded cells of myeloid lineage (Lyve-1-expressing macrophages) as a source of lymphatic endothelial progenitor during embryonic development and in tumor environment by demonstrating that macrophages bearing the Lyve-1 antigen were Prox-1-negative (Gordon et al, 2010). Various authors have reported that macrophages bearing the Lyve-1 antigen may contribute to neolymphangiogenesis during inflammation and tumor environment by producing proangiogenic stimuli, including growth factors: VEGF-A, VEGF-C, and VEGF-D (Schoppmann et al, 2002;Cursiefen et al, 2004;Baluk et al, 2005;Maruyama et al, 2007;Jeon et al, 2008;Kataru et al, 2009;Kim et al, 2009). The results by Gordon et al (2010) indicate that macrophages are not a major source of prolymphagniogenic factors in the skin.…”
Section: Developmental Dynamicsmentioning
confidence: 99%